National, international, and human security a comparative introduction - Neack, Laura (New millennium books in international studies, 2017)
This concise updated edition offers a clear and comprehensive comparison of national, international, and human security. Laura Neack frames key concepts and policies, paired with timely new case studies, arguing that security remains elusive due to a centuries-old ethic insisting that states are the only viable international actors.